Spatiotemporal dynamics of a peri-urban stream water quality and its relationship with land use - Valdiviezo Gonzales, Lorgio Gilberto (2023)
This study evaluated the impact of land use/land cover patterns on the water quality of a stream in a periurban zone. For this, the water quality was determined by the NSF-WQI, Dinius-WQI, and Heavy Metal Pollution Index (HPI). On the other hand, land uses were obtained from “RapidEye” satellite images, including green, urban, commercial and industrial areas. The land uses were grouped, and the different degrees of association with the chosen water quality parameters were found. The results indicated that the physicochemical parameters were negatively correlated with the “green areas” and positively correlated with the “intervened areas”.